Efektifitas Seduhan Kayu Manis Terhadap Kadar Gula Darah pada Pasien Diabetes Melitus di Kecamatan Kawangkoan Sulawesi Utara - Manorek, Drova Grano; Kallo, Vandry (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Analyzing the effectiveness of cinnamon infusion on reducing blood sugar levels in diabetes mellitus patients in Kawangkoan District, North Sulawesi. This study used a Quasy experiment design with a pre-post control group design approach. The total sample in the study was 23 respondents. The sampling technique was a non-random sampling technique used was accidental sampling. The instruments used were observation sheets and standard operating procedures for cinnamon infusion and data analysis tests used Repeated Measure Anova. The results of the analysis showed a p value <0.05, namely blood sugar levels during 4 days of evaluation of cinnamon infusion showed changes in mean values and significant values p value <0.000 so that it can be concluded that there is effectiveness of cinnamon infusion on blood sugar levels in diabetes mellitus patients with a 95% confidence level. It can be concluded that cinnamon infusion is effective in reducing blood sugar levels in type II DM patients.